Cross-sectional study on relationships between physical function and psychological readiness to return to sport after anterior cruciate ligament reconstruction - Aizawa, J.; Hirohata, K.; Ohji, S.; Ohmi, T.; Mitomo, S.; Koga, H.; Yagishita, K. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Information about specific factors of physical function that contribute to psychological readiness is needed to plan rehabilitation for a return to sports. The purpose of this study was to identify specific physical functions related to the psychological readiness of patients aiming to return to sports 6 months after reconstruction. We hypothesized that the knee strength is a factor related to the Anterior Cruciate Ligament-Return to Sport after Injury scale (ACL-RSI) cutoff score for a return to sports.